2011
DOI: 10.4103/0377-4929.85092
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Kirby-Bauer disk diffusion method for detecting meropenem resistance among non-fermenting gram-negative bacilli

Abstract: The KBDD method can be reliably used for routine testing of meropenem resistance in A. baumannii, A. lwoffii and P. aeruginosa. However, further studies are needed before employing this technique for detecting meropenem resistance in Pseudomonas spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…One of the standard assay methods for testing antimicrobial activity is the Kirby-Bauer method [24], also referred to as the disc diffusion method. A selective culture media were prepared in the antimicrobial assay container and subsequently streaked uniformly with the selected test microorganisms.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the standard assay methods for testing antimicrobial activity is the Kirby-Bauer method [24], also referred to as the disc diffusion method. A selective culture media were prepared in the antimicrobial assay container and subsequently streaked uniformly with the selected test microorganisms.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…A Kirby-Bauer [24] technique was used to screen the antimicrobial activity for the methanolic leaves of Allexis cauliflora.…”
Section: Test Organismsmentioning
confidence: 99%
“…The Kirby-Bauer method for studying antibiotic resistance is a very easy and reliable test, with few errors in determining resistance, including NFGNB and carbapenems [21,22]. Moreover, the test is run in a solid medium, as occurred with our MIC-dilution method used in disinfectants and antiseptics, permitting a better correlation.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…The Kirby-Bauer disk diffusion (KBDD) method is more economical and the standardized one used for testing susceptibility to most of the antibiotics. However, only a few studies have provided data on its reliability for testing carbapenems against ABC isolates (1,3).…”
mentioning
confidence: 99%
“…According to EUCAST breakpoints (Table 1), no discrepancy was found between the KBDD method and the Etest for all the three carbapenems, though minor error rates could not be calculated for doripenem, since intermediate breakpoints are not defined. Joseph et al (3) showed that the KBDD method can be reliably used for routine testing of meropenem in ABC isolates.…”
mentioning
confidence: 99%